2006
DOI: 10.1111/j.1540-5907.2006.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

The Institutional Context of Tolerance for Ethnic Minorities: A Comparative, Multilevel Analysis of Western Europe

Abstract: Drawing on recent insights in the nationalism and citizenship regime literatures, this article develops a macrotheoretical framework for understanding cross-national variations in tolerance of ethnic minorities. Specifically, it tests the hypothesis that the degree to which the dominant ethnic tradition or culture is institutionalized in the laws and policies of a nation-state affects citizen tolerance of ethnic minorities. Employing a multilevel regression model, it systematically tests the framework, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
287
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(301 citation statements)
references
References 33 publications
9
287
0
5
Order By: Relevance
“…Ethnic and civic conceptions of national citizenship, for example, are elements of such an ideological climate that exists both at the policy level and at the level of shared values and beliefs in national populations. Across 15 European countries, Weldon (2006) showed that individuals in countries with ethnic citizenship regimes-requiring shared ethnicity and ancestry for citizenship-were less willing to grant political rights to ethnic minorities than individuals in countries with civic citizenship regimes (i.e., assimilationist and pluralistic regimes).…”
Section: Ideological Climate and Immigration Attitudesmentioning
confidence: 99%
“…Ethnic and civic conceptions of national citizenship, for example, are elements of such an ideological climate that exists both at the policy level and at the level of shared values and beliefs in national populations. Across 15 European countries, Weldon (2006) showed that individuals in countries with ethnic citizenship regimes-requiring shared ethnicity and ancestry for citizenship-were less willing to grant political rights to ethnic minorities than individuals in countries with civic citizenship regimes (i.e., assimilationist and pluralistic regimes).…”
Section: Ideological Climate and Immigration Attitudesmentioning
confidence: 99%
“…Since Quillian's (1995) first cross-national study of attitudes towards immigrants, there have been numerous analyses focusing on country comparisons (Pettigrew 1998;Scheepers et al 2002;Mayda 2006;Semyonov et al 2006;Weldon 2006;Hainmueller and Hiscox 2007;Meuleman et al 2009;Pichler 2010;Rustenbach 2010). Most of these studies test aggregate sources of competition at the regional and/or national level.…”
Section: Empirical Findings: the Local Contextmentioning
confidence: 99%
“…A nation's overall tolerance score may be a key to better understand its role in the global community (Das et al, 2008;Weldon, 2006). We add value to the tolerance literature by utilizing a large cross-country sample to develop an aggregate GSTI that incorporates four theory-based tolerance indicators, and expand it using multiple derivation methods of indexing and ranking, avoiding any weight assumptions and providing measures assessing each country's rank sensitivity or robustness.…”
Section: Discussionmentioning
confidence: 99%
“…An exception is Weldon's (2006) study of ethnic minority tolerance that focused a section on how citizenship regimes can affect social and political tolerances using 1997 Eurobarometer survey items. We fill this gap by deriving an immigration factor within our overall GSTI.…”
Section: Immigrationmentioning
confidence: 99%
See 1 more Smart Citation